1995
DOI: 10.1073/pnas.92.11.4758
|View full text |Cite
|
Sign up to set email alerts
|

Aod1, the immunoregulatory locus controlling abrogation of tolerance in neonatal thymectomy-induced autoimmune ovarian dysgenesis, maps to mouse chromosome 16.

Abstract: Mice thymectomized at three days of age (D3Tx) develop during adulthood a variety of organ-specific autoimmune diseases, including autoimmune ovarian dysgenesis (AOD). The phenotypic spectrum ofAOD is characterized by the development ofanti-ovarian autoantibodies, oophoritis, and atrophy. The D3Tx model ofAOD is unique in that disease induction depends exclusively on perturbation of the normal developing immune system, is T-cell-mediated, and is strain specific. For example, D3Tx A/J mice are highly susceptibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 19 publications
(24 reference statements)
2
29
1
1
Order By: Relevance
“…Aod1, involved in neonatal thymectomy-induced autoimmune ovarian dysgenesis, has been mapped on mouse Chr 16 (25). The map position of Aod1 seemed to be proximal to Gap43 (25), while Iddm/ kdp1 would be located in the region distal to Gap43, which weakened a possible relationship between Aod1 and Iddm/ kdp1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aod1, involved in neonatal thymectomy-induced autoimmune ovarian dysgenesis, has been mapped on mouse Chr 16 (25). The map position of Aod1 seemed to be proximal to Gap43 (25), while Iddm/ kdp1 would be located in the region distal to Gap43, which weakened a possible relationship between Aod1 and Iddm/ kdp1.…”
Section: Discussionmentioning
confidence: 99%
“…Aod1, involved in neonatal thymectomy-induced autoimmune ovarian dysgenesis, has been mapped on mouse Chr 16 (25). The map position of Aod1 seemed to be proximal to Gap43 (25), while Iddm/ kdp1 would be located in the region distal to Gap43, which weakened a possible relationship between Aod1 and Iddm/ kdp1. The others include Ly7 (lymphocyte antigen-7), CD80 (CD80 antigen, also known as CD28 antigen ligand 1 or B7-1 antigen), CD47 (CD47 antigen, also known as Rh-related antigen, integrin-associated protein, or MER6 antigen identified by mAb 1D8), and MOX2 (antigen identified by mAb MRC OX-2) (24,26).…”
Section: Discussionmentioning
confidence: 99%
“…PREMATURE OVARIAN FAILURE AND OVARIAN AUTOIMMUNITYthymectomy day 3 (284). This so-called Aod1 locus was associated with the presence of oö phoritis in the mice.…”
Section: February 1997mentioning
confidence: 98%
“…Interestingly, the markers on chromosome 16 failed to exhibit a significant linkage to the concomitant ovarian atrophy in this mouse oö phoritis model. Rather, this atrophy exhibited an association with markers on mouse chromosome 3 (284). With regard to another experimental mouse model of gonadal autoimmunity, viz the male counterpart of allergic oö phoritis, experimental allergic orchitis, studies have shown a similar complexity of gene involvement and the recognition of various susceptibility and resistance loci (the Orch genes) (285).…”
Section: February 1997mentioning
confidence: 99%
“…Silveira et al (8) showed that two loci on chromosome 4, Gasa1 and Gasa2, control susceptibility to autoimmune gastritis after D3Tx. In a previous study, we reported that susceptibility to autoimmune ovarian dysgenesis (AOD) is controlled by loci on chromosome 16 (Aod1) and chromosome 3 (Aod2) (9,10).…”
Section: Interacting Quantitative Trait Loci Control Loss Of Periphermentioning
confidence: 99%